(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Kalanganyar is a village that is famous for its milkfish processing business, with so many processed milkfish, a lot of waste is generated from the manufacturing process. Liquid organic fertilizer is a solution from the decomposition of organic materials derived from plant residues, animal and human wastes which contain more than one nutrient element. With the socialization of the manufacture of liquid organic fertilizer, it can reduce waste waste, improve the people’s economy and encourage the creation of a law and order environment. This community service activity is in the form of socialization and training on the manufacture of liquid organic fertilizer in Kalanganyar Village. With the socialization to the public about the manufacture of organic liquid fertilizer